Hot compression deformation behavior of MB26 magnesium alloy - 杜志惠 张绪虎 方西亚 张晓娟 陈永来 张宇玮 (Transactions of Nonferrous Metals Society of China, 2007)
The flow stress features of MB26 magnesium alloy were studied by isothermal compression at 300-450 ℃ and strain rate of 0.001^-1 s J with Gleeble 1500 thermal simulator. In addition, the deformation activation energy Q was calculated. The results show that the strain rate and deformation temperature have obvious effect on the true stress. The peak value of flow stress becomes larger with increasing strain rate at the same temperature, and gets smaller with the increasing deformation temperature at the same strain rate. The alloy shows partial dynamic recrystallization. The flow stress of MB26 magnesium alloy during high temperature deformation can be represented by Zener-Hollomon parameter including the Arrhemius term. The temperatt, re range of 350-400℃ is suggested for hot-forming of this alloy.